Comprehensive Evaluation Of Law Enforcement Against Embezzlement Due To Position Case Study: Decision 315/Pid.B/2023/Pn.Gsk - Rakmahwati Pratiwi, Indy; Abdullah, Saiful (Dinasti Research, 2024)
Abuse is a willful and unlawful act of taking someone else's property. This crime is characterized by a breach of trust and often occurs at various social levels. By raising the legal issue of the crime of embezzlement committed by Dwi Zahrul Fitriana Binti Djumadi Hari Santoso (deceased) who was committed during her term of office as a result of employment, search, or receiving wages in case number 315/Pid.B/2023/PN Gsk. This study examines thoroughly the criminalization of fraud in the term of office of Dwi Zahrul Fitriana Binti Djumadi Hari Santoso (expired) so that later the local area will be more careful in acting. This research uses an empirical legal approach method. The examination used is a subjective examination. The verdict determined that the defendant had taken funds from PT Cipta Mandiri Nusantara Abadi and did not return them. The defendant was found guilty of the charges of the panel of judges and sentenced to two years and six months in prison for violating the Criminal Procedure Code and Article 374 of the Criminal Code. The Panel of Judges' considerations, including aggravating and mitigating circumstances, have met the principles of legal certainty, justice, and expediency, in accordance with empirical analysis.